Vitrectomy in an eye with unsuspected retinoblastoma (Ukrainian Journal of Ophthalmology, 2026)
Background. Retinoblastoma (Rb) cases with atypical clinical manifestations, which lead to error diagnosis and inadequate treatment, have become more frequent over the last years.Purpose. To describe and to analyze a clinical picture, diagnostics, and treatment of vitrectomy performed in an eye with unsuspected Rb resulted in pre-operational diagnostic error. Material and Methods. A patient B., aged 5 years 7 months, with unsuspected Rb in the right eye was performed pars plana vitrectomy in local health facilities.Results. After vitrectomy, pseudohypopyon, silicone oil, and cataract were observed in the anterior chamber of the right eye. Ultrasound scanning was not informative due to a shadowing effect of the silicone oil in the vitreous. Fine needle aspiration of pseudohypopyon revealed a great number of cells, supposedly, of retinoblastoma or retinal lymphoma. It was magnetic resonance tomography that could reveal the signs of tumor. The right eye was enucleated. Pathohistological examination showed undifferentiated multifocal Rb with tumor nodules in the optic nerve in equator and with 1-2.0 mm invasion in the choroid in the optic nerve within the cribiform plate. Adjuvant polychemotherapy (carboplatin-etoposide-vincristine protocol) and gamma-ray teletherapy were prescribed to prevent hematogenous metastasis and orbital recurrence of retinoblastoma.Conclusions. Vitreactomy in the eyes with untreated Rb contributes to tumor cell seeding in the numerous eye structures and can affect the survival.
Keywords: unsuspected retinoblastoma; vitrectomy; pseudohypopyon; enucleation